You are watching: 6x^2-13x+6
This equation is in standard form: ax^2+bx+c=0. Instead of 6 for a, 13 for b, and also -6 for c in the quadratic formula, \frac-b±\sqrtb^2-4ac2a.
6x2+13x-63=0 Two remedies were uncovered : x = -9/2 = -4.500 x = 7/3 = 2.333 step by step solution : action 1 :Equation at the end of action 1 : ((2•3x2) + 13x) - 63 = 0 step 2 :Trying come ...
5x2+13x-6=0 Two services were uncovered : x = -3 x = 2/5 = 0.400 action by action solution : step 1 :Equation in ~ the finish of action 1 : (5x2 + 13x) - 6 = 0 step 2 :Trying to factor by dividing ...
6x2+13x+6=0 Two solutions were uncovered : x = -3/2 = -1.500 x = -2/3 = -0.667 step by action solution : step 1 :Equation in ~ the end of action 1 : ((2•3x2) + 13x) + 6 = 0 step 2 :Trying to ...
exactly how do you discover the genuine or imaginary remedies of the equation \displaystyle6x^2+13x-5=0 ?
The services are\displaystyleS=\left\lbrace\frac13,-\frac52\right\rbrace Explanation:The coincided equations\displaystyleax^2+bx+c=0 ours equation ...
(15x2)+13x-6=0 Two options were found : x = -6/5 = -1.200 x = 1/3 = 0.333 action by step solution : action 1 :Equation at the end of step 1 : ((3•5x2) + 13x) - 6 = 0 action 2 :Trying to ...
6x2+3x-63=0 Two solutions were found : x = -7/2 = -3.500 x = 3 action by step solution : action 1 :Equation in ~ the finish of step 1 : ((2•3x2) + 3x) - 63 = 0 step 2 : action 3 :Pulling out choose ...
All equations that the type ax^2+bx+c=0 have the right to be resolved using the quadratic formula: \frac-b±\sqrtb^2-4ac2a. The quadratic formula gives two solutions, one once ± is addition and one as soon as it is subtraction.
This equation is in standard form: ax^2+bx+c=0. Instead of 6 because that a, 13 for b, and also -6 for c in the quadratic formula, \frac-b±\sqrtb^2-4ac2a.
Quadratic equations such together this one deserve to be solved by completing the square. In stimulate to finish the square, the equation must an initial be in the kind x^2+bx=c.
Divide \frac136, the coefficient the the x term, by 2 to obtain \frac1312. Then add the square the \frac1312 come both sides of the equation. This step provides the left hand next of the equation a perfect square.
See more: What Is The Difference Between A Hexagon And An Octagon ? What Is Octagon
Factor x^2+\frac136x+\frac169144. In general, once x^2+bx+c is a perfect square, that can constantly be factored together \left(x+\fracb2\right)^2.
Quadratic equations such as this one deserve to be resolved by a brand-new direct factoring method that walk not need guess work. To usage the direct factoring method, the equation need to be in the type x^2+Bx+C=0.This is completed by dividing both sides of the equation through 6
Let r and s it is in the factors for the quadratic equation such that x^2+Bx+C=(x−r)(x−s) where amount of determinants (r+s)=−B and also the product of components rs = C
Two numbers r and s sum up to -\frac136 precisely when the median of the 2 numbers is \frac12*-\frac136 = -\frac1312. You can additionally see that the midpoint that r and also s corresponds to the axis of the opposite of the parabola represented by the quadratic equation y=x^2+Bx+C. The worths of r and s space equidistant from the facility by one unknown quantity u. Refer r and s v respect to variable u.
EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు